Diverse Cis-Regulatory Mechanisms Contribute to Expression Evolution of Tandem Gene Duplicates - Baudouin-Gonzalez, Luís (2018)
The deposited article is a post-print version and has peer review. The deposited article version contains attached the supplementary materials within the pdf.